Development of massive multilevel molecular dynamics simulation program, platypus (PLATform for dYnamic protein unified simulation), for the elucidation of protein functions. Issue 12 (4th March 2016) - Takano, Yu; Nakata, Kazuto; Yonezawa, Yasushige; Nakamura, Haruki
Abstract : A massively parallel program for quantum mechanical‐molecular mechanical (QM/MM) molecular dynamics simulation, called Platypus (PLATform for dYnamic Protein Unified Simulation), was developed to elucidate protein functions. The speedup and the parallelization ratio of Platypus in the QM and QM/MM calculations were assessed for a bacteriochlorophyll dimer in the photosynthetic reaction center (DIMER) on the K computer, a massively parallel computer achieving 10 PetaFLOPs with 705, 024 cores. Platypus exhibited the increase in speedup up to 20, 000 core processors at the HF/cc‐pVDZ and B3LYP/cc‐pVDZ, and up to 10, 000 core processors by the CASCI(16, 16)/6‐31G** calculations. We also performed excited QM/MM‐MD simulations on the chromophore of Sirius (SIRIUS) in water. Sirius is a pH‐insensitive and photo‐stable ultramarine fluorescent protein. Platypus accelerated on‐the‐fly excited‐state QM/MM‐MD simulations for SIRIUS in water, using over 4000 core processors. In addition, it also succeeded in 50‐ps (200, 000‐step) on‐the‐fly excited‐state QM/MM‐MD simulations for the SIRIUS in water. © 2016 The Authors. Journal of Computational Chemistry Published by Wiley Periodicals, Inc. Abstract : A massively parallel program for on‐the‐fly quantum mechanical‐molecular mechanical (QM/MM) molecular dynamics simulations, Platypus (PLATform for dYnamic Protein Unified Simulation), was developed for the elucidation of protein functions. The performances of Platypus were assessed for bacteriochlorophyll dimer and the chromophore of Sirius, a pH‐insensitive and photo‐stable ultramarine fluorescent protein, in water on the K computer. Platypus succeeded in massively parallel computations, using more than 10, 000 core processors.